Methods of synthesis and formation of a system of nonlinear discrete signals for modern information and communication systems - Gorbenko, I.D.; Zamula, A.A.; Luc, Ho Tri (Radiotekhnika, 2020)
The paper presents the results of solving the urgent problem of improving the performance indicators of information and communication systems (ICS), in particular, information security, noise immunity, secrecy, the speed of formation and processing of information. The use of the distributed spectrum technology (broadband noise-like signals) is a promising direction for ensuring the security of information resources. The methods used for data formation and processing, as well as the classes of broadband signals used as physical data carriers, do not allow providing the necessary (especially for critical infrastructure facilities) indicators of information security and noise immunity. In this case, as discrete sequences (DS) that expand the spectrum (manipulate the carrier frequency), should be used DS based on nonlinear construction rules and having improved correlation, ensemble and structural properties. Methods for the synthesis and formation of nonlinear discrete complex signals, namely, the so-called cryptographic signals, are proposed. The first method, presented in the article, uses random (pseudo-random) processes. Another method is based on the implementation of the operation of decimation of the original discrete sequence of symbols obtained from the results of the implementation of the first method; it provides the synthesis of an ensemble of signals for a certain signal duration. Analytical expressions are obtained for determining the synthesis time of an ensemble of signals using the proposed methods. It is shown that the speed of the signal generation method based on the decimation operation for a certain signal duration is more than three orders of magnitude higher than the speed of the method based on the random (pseudo-random) processes used. At the same time, based on the carried out computer simulation, it is shown that the signals obtained using the proposed methods have identical correlation, ensemble, and structural properties.